Marginalised Australians: Characteristics and Predictors of Exit Over Ten Years 2001-10 - Cruwys, T.; Berry, H.; Cassells, R.; Duncan, Alan; O'Brien, L.; Sage, B.; D'Souza, G. (University of Canberra, 2013)
A decade ago a group of ‘Marginalised’ Australians were identified; individuals who are characterised by a complex mix of financial, social, and mental health disadvantage. This project has followed up these individuals ten years later, and found that a majority have managed to escape from marginalisation. It is important to tell these people’s stories in order to identify the protective factors that predict exit from such a disadvantaged state, and subsequently learn how policy might further support vulnerable Canberrans.